Hidden in Plain Sight: Uncovering an Accessory Piriformis Muscle as the Root Cause of Piriformis Syndrome - Dayang Corieza Febriany; Nur Yazmin Yaacob; Suraya Aziz (Gazi University Medical Faculty, 2023)
Piriformis syndrome is an extremely uncommon condition that results in sciatic nerve entrapment at the level of the piriformis muscle, which leads to excruciating pain in the lower back, buttocks, and leg. An abnormal condition of the piriformis muscle, such as hypertrophy, inflammation, or anatomical abnormalities, is the most common root cause of this problem. We discuss the case of a 46-year-old woman with right gluteal pain and sciatic neuropathy who was diagnosed with piriformis syndrome as a result of an accessory pyriformis muscle that was discovered by magnetic resonance imaging (MRI).